2010
DOI: 10.1161/atvbaha.110.209775
|View full text |Cite
|
Sign up to set email alerts
|

Apelin Is a Crucial Factor for Hypoxia-Induced Retinal Angiogenesis

Abstract: Objective-To investigate the role of endogenous apelin in pathological retinal angiogenesis. Methods and Results-The progression of ischemic retinal diseases, such as diabetic retinopathy, is closely associated with pathological retinal angiogenesis, mainly induced by vascular endothelial growth factor (VEGF) and erythropoietin. Although antiangiogenic therapies using anti-VEGF drugs are effective in treating retinal neovascularization, they show a transient efficacy and cause general adverse effects. New ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 29 publications
6
68
0
1
Order By: Relevance
“…Significantly, apelin is required for the normal development of frog heart (Cox et al 2006, Inui et al 2006 and formation of murine blood vessels (Kidoya & Takakura 2012). Additionally, the development of the retinal vasculature is stunted in apelin KO mice (Kasai et al 2008), and apelin is necessary for hypoxia-induced retinal angiogenesis (Kasai et al 2010), and is also involved in non-neovascular remodelling of the retina (McKenzie et al 2012). The apelinergic system has been implicated in tumour neoangiogenesis.…”
Section: Role Of Apelin/apj In Angiogenesismentioning
confidence: 99%
“…Significantly, apelin is required for the normal development of frog heart (Cox et al 2006, Inui et al 2006 and formation of murine blood vessels (Kidoya & Takakura 2012). Additionally, the development of the retinal vasculature is stunted in apelin KO mice (Kasai et al 2008), and apelin is necessary for hypoxia-induced retinal angiogenesis (Kasai et al 2010), and is also involved in non-neovascular remodelling of the retina (McKenzie et al 2012). The apelinergic system has been implicated in tumour neoangiogenesis.…”
Section: Role Of Apelin/apj In Angiogenesismentioning
confidence: 99%
“…During recent years, apelin has gained increasing attention in the function of angiogenesis, especially in retinal neovascularization. Kasai and others' studies [4,5] found that apelin is a crucial factor for retinal angiogenesis in prematurity of retinopathy (ROP) mice and apelin-deficiency can retard the retinal vascular development. In in vivo study, the sizes of the laser induced CNV lesions in apelin-KO or APJ-KO mice decreased significantly compared with those in the WT mice [6].…”
mentioning
confidence: 99%
“…Furthermore, it was reported [14] that treatment of human umbilical vein endothelial cells with apelin increased endothelial cell migration and proliferation in a dose-dependent manner. Apelin suppressed the proliferation of endothelial cells independently of the vascular endothelial growth factor VEGF/VEGF receptor and appeared to be a prerequisite factor for hypoxia-induced retinal angiogenesis [21]. Based on these results, it seems that apelin can affect the cell cycle interacting with phosphatidylinositol 3 kinase (PI3-K) pathway activity, but more detailed data are needed to determine the signalling pathway involved in apelin action in IEC-6 and Caco-2 cell lines used in our study.…”
Section: Discussionmentioning
confidence: 94%
“…The apelin was found to stimulate [12][13][14][15] or inhibit [21] cell proliferation, depending on a cell line. Wang and co-workers [9] showed that apelin stimulated cell proliferation in human gastric epithelial cell line SIIA, while Han et al, [22] reported that acute exposure of rat pups to hypoxia decreased gastric and colonic epithelial cell proliferation, while hypoxia in combination with apelin administration resulted in increased proliferation of epithelial cells and improved cell survival [22].…”
Section: Discussionmentioning
confidence: 99%